Contemporary Spanish theatre from a gender perspective: the news as a complaint in Si en el árbol un burka (2016) by María Velasco - Romero Morales, Yasmina; Hernández Rodríguez, Ana Isabel (Talía. Revista de estudios teatrales, 2021)
This article has two main interests, to see the close and productive relationship between the mass media and the dramaturgical in contemporary Spanish literature, especially in theatre; and, secondly, to see how this relationship serves María Velasco in her text Si en el árbol un burka (2016) for two purposes, the main one, to denounce violence against women and, then, as a strategy to deconstruct gender roles. The methodology used for the development of this research has been the product of the encounter of feminist literary criticism, theatrical theory and cultural studies.
Keywords: María Velasco; contemporary Spanish theatre; theatre and gender; gender violence; literature and press